2017
DOI: 10.3389/fphys.2017.00248
|View full text |Cite
|
Sign up to set email alerts
|

Association between Carotid Intima Media Thickness and Heart Rate Variability in Adults at Increased Cardiovascular Risk

Abstract: Background: Atherosclerotic carotid intima-media thickness (IMT) may be associated with alterations in the sensitivity of carotid baroreceptors. The aim of this study was to investigate the association between carotid IMT and the autonomic modulation of heart rate variability (HRV).Methods: A total of 101 subjects were enrolled in this prospective observational study. The carotid IMT was determined by duplex ultrasonography. The cardiac autonomic function was determined through HRV measures during the Deep Bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…Then, this work sought to investigate whether there is an independent relationship between cIMT and HRV. Agreeing with this, Pereira et al (2017) reported higher cIMT in the lowest quartile of SDNN and a progressive decline in the subsequent quartiles in adults at increased cardiovascular risk during a deep breath test. This lack of association may suggest that besides dependents on several factors, these measures assess different and complementary domains of cardiovascular risk, providing important, useful and non-redundant information for clinical and scientific purposes.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Then, this work sought to investigate whether there is an independent relationship between cIMT and HRV. Agreeing with this, Pereira et al (2017) reported higher cIMT in the lowest quartile of SDNN and a progressive decline in the subsequent quartiles in adults at increased cardiovascular risk during a deep breath test. This lack of association may suggest that besides dependents on several factors, these measures assess different and complementary domains of cardiovascular risk, providing important, useful and non-redundant information for clinical and scientific purposes.…”
Section: Discussionsupporting
confidence: 52%
“…Atherosclerosis is the main underlying cause of cardiovascular diseases and is characterized by the presence of atheromatous plaques in the arterial wall and increased intima-media (Huikuri et al, 1999;Stein et al, 2008;Pereira et al, 2017;Ulleryd et al, 2017). Carotid intima-media thickness (cIMT) is a an important marker for subclinical vascular disease and an indicator of systemic inflammation, considered a surrogate outcome for atherosclerotic disease (Stein et al, 2008;Santos et al, 2014;Generoso et al, 2018;Sena et al, 2018;Holwerda et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…Depression has been closely associated with autonomic nervous system dysfunction, with reduced parasympathetic and/or increased sympathetic activity leading to increased cardiovascular risk in depressed patients ( 32 34 ). In line with these findings, increased inter-lead QT interval differences on 12-lead electrocardiography (QT dispersion) or reduced heart rate variability (HRV) has been reported in depressed patients ( 19 , 35 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Decreasing serotonin may cause a decrease in parasympathetic activity ( 58 ), and emotional response capabilities are marked peripherally by vagal efference to the heart ( 40 , 59 ). Specifically, high parasympathetic tone helps to maintain heart stability and protect against possible adverse cardiac events ( 32 , 34 ). Conversely, increased sympathetic tone increases the risk of malignant arrhythmias and sudden cardiac death ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…The FHR variability was determined using coefficient of variation (CV), which equals the standard deviation divided by the mean ( Pereira et al, 2017 ). The characteristics of study participants were depicted using standard descriptive statistics, overall and stratified by quartiles of the mean of FHR.…”
Section: Methodsmentioning
confidence: 99%